Peran Cerita Rakyat terhadap Pembentukan Karakter Anak: Analisis Sastra dan Psikologi - Dewi, Dewi; Nurzaman, Bela (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2024)
Folklore is an important part of cultural heritage that contains moral and social values. In the context of education, folklore not only serves as entertainment, but also as an effective learning medium to shape children's character. This article discusses the influence of folklore on children's character building through literary and psychological approaches. This research uses a qualitative method, the analysis is done by reviewing relevant literature and research. The results show that folktales are able to instil moral values, strengthen cultural identity, and develop empathy and tolerance in children. In addition, the emotional impact produced by folktales strengthens the internalisation of these values in children, making them an important tool in character education. This article recommends the wider utilisation of folklore in education to strengthen children's character building.